Technological Factors of Cloud Computing Adoption Model for Malaysian Small and Medium Enterprises (SMEs) - Abdulgadr, Abdulhafid Bughari Abdulkarim; Elbakai, Salem El-Bahlool (International Journal of Computer Sciences and Engineering, 2020)
Cloud computing (CC) provides an economy of scale, efficient resources usage, and the availability of the resources to a large user base. Despite the provision of electronic infrastructure by Malaysian government and spending billions of dollars annually for cloud computing adoption, its level among SMEs is still low. Therefore, the key objective of the current research is to propose a cloud computing adoption model to determine technology attributes that affect the adoption in Malaysian SMEs, as technology component suffers the most significant threat against cloud adoption. The research model is based on Technology Organization Environment Framework (TOE) and its extended conceptual model by Opala. The technology factors include service level, security, cost effectiveness, IT compliance, reliability, flexibility and confidentiality. The primary data collection was conducted using the survey method. A total of 225 questionnaires were collected from IT Executives of the SMEs in Malaysia. Quantitative data was analyzed statistically using SPSS and AMOS software version 21. The results of the data analysis show that the exogenous variables, reliability, confidentiality, flexibility, service level explained 69% of the variance in security effectiveness and explained 41% of the variance in cost effectiveness as well as explained 33% of the variance in IT compliance.